Individual Assignments (Business Plan) ENT 300 : Lovely Kurung Cotton / Nur Syaza Aufa Sabri - Sabri, Nur Syaza Aufa (2020)
Lovely Kurung Cotton is a small company in Kedah managed by Nur Syaza Aufa herself at the first place. We are aiming for all types of baju kurung that will surely bring comfortable to our customers. We focused more on the material to make sure that we achieves our standards of baju kurung. We really care about our brands in the eyes of customers.